The Factors Associated with Ownership of Health Insurance Among Women of Reproductive Health in Guyana - Rusmitasari, Heni; Santoso, Eko Budi; Supriatin, Supriatin; Maretalinia, Maretalinia (Unnes Journal of Public Health, 2024)
Women of reproductive age are one vulnerable group because of the phase of pregnancy, childbirth, and contraceptive use. Due to those reasons, they need to be covered by health insurance. However, the coverage of health insurance remains low, especially in developing countries including Guyana. This study aimed to examine the factors associated with ownership of health insurance among women of reproductive age. This study used the data from Multiple Indicators Cluster Survey Wave 6 (MICS6) Guyana in 2019-2020. Totally, 5,470 women met the criteria. The multivariate analysis was done by 2 models including the community characteristics. It was found some factors related to having or not having health insurance, including living in Damerara-Mahaica and Mahaica-Berbice regions, having Muslim, female, and from Amerindian, East Indian, and Mixed ethnic of household head, having a higher wealth index and education level, aged 30-34, and formerly marriage or never married. The health insurance scheme needs to be arranged especially at tat regional level to ensure women can access maternal services easily and effectively.